Using differentiated instruction in multigrade classes: a case of a small school. Issue 1 (2nd January 2021) - Shareefa, Mariyam
ABSTRACT: This paper presents findings of a case-study set in one of the small schools of Maldives which was practising the concept of multigrade teaching. The aim of the study was to investigate teachers' experiences of using Differentiated Instruction (DI) in multigrade classes. It also explored the benefits as well as challenges for using DI in the combined classes. Participants of the study included the school principal and four respective teachers who were teaching in multigrade classes. Data for the study were obtained through semi-structured interview, classroom observation and document analysis of teachers' lesson plans. Findings indicate a high level of differentiated instruction taking place in the multigrade classes displaying numerous benefits that were positively related to students' academic progress as well as students' psychosocial development. Findings also revealed teachers' lack of competency, lack of time for high workload and assessment of student learning as major challenges that hamper the use of DI. Several practical implications for teachers, teacher educators and school leaders are discussed in the paper.